Manifestasi Klinis dan Neuroimaging Pada Sindrom Dandy Walker - Irbi Eki Habibi; Andriyani Andriyani (STIKES Columbia Asia Medan, 2024)
Dandy Walker syndrome is a rare malforation of the central nervous system characterized by expansion of the fourth ventricle, widening of the posterior fossa, agenesis or dysplasia of the cerebellar vermis accompanied by upward dislocation. This disease occurs more often in women and the etiology is still unknown, but it is related to a combination of genetic and environmental factors. Dandy Walker syndrome is often not detected initially unless clinical manifestations in the form of hydrocephalus occur. This is interesting to discuss considering the low diagnosis of Dandy Walker Syndrome. Diagnosis is based on clinical symptoms and radiological images on antenatal ultrasound, CT scan and MRI. Management of Dandy Walker Syndrome can include surgery to reduce hydrocephalus, physical and occupational therapy, and pharmacotherapy to control neurological symptoms. The lack of diagnosis of Dandy Walker Syndrome makes this an interesting matter to review in the literature.